MODEL DIALOG “4D” UNTUK MENINGKATKAN KESADARAN MULTI KULTURAL SISWA SMA DI KOTA MALANG - Hambali, IM (Jurnal Kajian Bimbingan dan Konseling, 2016)
A counselor will be said to be professional if he is able to master the concepts and practice of assessment to understand students' conditions, needs and problems, master the theoretical and practical framework of Guidance and Counseling (BK), design a BK program, implement a comprehensive BK program, assess the process and results of BK activities , have awareness and commitment to professional ethics and master the concepts and practice of research in BK. This research is development research. The needs analysis stage was carried out using the survey method. However, in reality there are still many counselors who have not mastered all of the above competencies. This is also due to the large number of duties and responsibilities of school counselors in dealing with student problems compared to the number of counselors in schools. Ideally one counselor handles 150 students at school (Permendiknas No. 27 of 2008). However, in reality in the field, based on observations at several high schools (SMA) in the city of Malang, counselors hold more than 150 students and some even hold more than 500 students. From the description of the data as presented, it can be concluded as follows. (1) Many counselors complain about the school atmosphere which does not allow counselors to carry out counseling well, (2) Counselors need alternative individual service strategies because they have difficulty applying counseling approaches in all situations, (3) Counselors must be creative in implementing counseling services and strategies to provide good service to students.